La langue berbère au Maghreb médiéval : textes, contextes, analyses - Meouak, Mohamed (Brill, 2015)
La langue berbe¿¿re au Maghreb me¿¿die¿¿val constitue un nouvel apport aux e¿¿tudes historiques et linguistiques dans la mesure ou¿¿ de nombreux mate¿¿riaux sur la langue berbe¿¿re font l¿́¿objet d¿́¿une monographie spe¿¿cifique. Plusieurs faits de langue sont relie¿¿s par une trame pre¿¿cise et ils sont re¿¿unis afin de mettre en relief les indices textuels puise¿¿s dans diverses sources e¿¿crites en arabe et en berbe¿¿re. Dans les quatre parties du livre, il est tour a¿¿ tour question des apports de la documentation narrative, de la litte¿¿rature hagiographique et des textes ibadites ainsi que de l¿́¿importance des contacts entre le berbe¿¿re et les langues africaines a¿¿ travers la litte¿¿rature narrative et l¿́¿e¿¿pigraphie islamique. Ce livre a e¿¿te¿¿ conc¿ʹu comme un essai documentaire mais e¿¿galement afin d¿́¿attirer l¿́¿attention des chercheurs sur la pre¿¿sence relativement bien documente¿¿e de la langue berbe¿¿re dans les textes produits en milieu arabo-musulman du Moyen A¿¿ge a¿¿ l¿́¿e¿¿poque moderne. La langue berbe¿¿re au Maghreb me¿¿die¿¿val is a new contribution to the historical and linguistic studies in that many materials on the Berber language are the subject of a specific monograph. Several facts of language are connected by an accurate frame and are gathered to highlight textual clues collected from various sources written in Arabic and Berber. The four parts of the book treat contributions of narrative documentation, hagiographical literature and Ibadi texts and the importance of contacts between Berber and African languages through the narrative literature and Islamic epigraphy. This book was conceived as a documentary essay, but also to attract the attention of researchers on the relatively well-documented presence of the Berber language in the texts produced in Arab-Muslim environment from the Middle Ages to Modern era.
Keywords: Berber languages.; Africa, North -- History -- 647-1517.; Langues berbères.; Afrique du Nord -- Histoire -- 647-1517.; FOREIGN LANGUAGE STUDY -- African Languages.; Berber languages; North Africa; 647-1517; History